2009
DOI: 10.4103/0256-4947.55306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of extended-spectrum β-lactamase-producing Klebsiella pneumoniae in Riyadh, Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVES:Reports on extended-spectrum β-lactamases (ESBL) production by Enterobacteriaceae, and especially in Klebsiella pneumoniae, are few in Saudi Arabia. Therefore, we determined the prevalence of ESBL in K pneumoniae from Riyadh and characterized the predominant β-lactamase gene in these isolates.METHODS:A total of 400 K pneumoniae samples were isolated from two hospitals in Riyadh during 2007 and screened for production of ESBL using ESBL-E-strips and combined disk methods. PCR assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 32 publications
11
67
12
Order By: Relevance
“…Similar results have been obtained in many studies in India and other countries [7]. In a study conducted from 10 Indian sites in six Indian cities by Welsh et al, [24] bla CTX-M was the most common genotype isolated.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Similar results have been obtained in many studies in India and other countries [7]. In a study conducted from 10 Indian sites in six Indian cities by Welsh et al, [24] bla CTX-M was the most common genotype isolated.…”
Section: Resultssupporting
confidence: 72%
“…Similar results have been documented in Europe, Latin America and other countries [25]. The CTX-M genotype, originating from chromosomally encoded enzymes of the Kluyvera spp, has risen in predominance especially in Escherichia coli and Klebsiella pneumoniae they have greater ability to spread and cause outbreaks [7].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…A 2007 study from two hospitals in Riyadh reported that 97.3% of K. pneumoniae isolates carried bla SHV -like genes, followed by 84.1% carrying bla TEM genes and 34.1% carrying bla CTX-M -like genes. Further PCR screening revealed that 60% of the CTX-M-positive isolates carried bla CTX-M-1 -like genes and the other 40% carried bla CTX-M-9 -like genes (16). In April 2005, an outbreak occurring at a neonatal ward in Riyadh was due to an SHV-12-producing K. pneumoniae strain (17) (Table 3), which is prevalent in other parts of the world (18)(19)(20).…”
Section: Extended-spectrum and Ampc-type ␤-Lactamasesmentioning
confidence: 99%
“…[13][14][15][16][17] Rates of 31.7% and 41% have been reported in neighbour Gulf Countries like Kuwait [18] and the United Arab Emirates [19] respectively. In Saudi Arabia, bla TEM , bla SHV and bla CTX-M have been reported in clinical isolates of Enterobacteriaceae in Riyadh [20,21] , Dammam [11] , and Dhahran. [22,23] In the present study, the prevalence of bla TEM , bla SHV and bla CTX-M in E. coli clinical isolates is reported for the first time in Taif governorate.…”
Section: Introductionmentioning
confidence: 99%